Company Value and Operating Profit Margin in the Energy Sector vs. PTBA vs. PGAS - Sri Suryaningrum; Juman Sahbandi; Sutoyo Sutoyo; Sujatmika Sujatmika (AIBPM Publisher, 2025)
This paper aims to provide a benchmark for average company value and operating profit margins in the energy sector. This paper analyzes the average company value and operating profit margin in the energy industry sector from 2021 to 2024 and compares them with those of PT Bukit Asam Tbk (PTBA) and PT Perusahaan Gas Negara Tbk (PGAS). The research method used is descriptive quantitative comparative analysis. Secondary data were obtained from annual financial reports and publications of the Indonesia Stock Exchange for the 2021–2024 period in the energy sector for 191 energy sector companies. The results show that the average company value across the energy sector from 2021 to 2024 was 1.56, while the average company value for PTBA was 1.53 and the average company value for PGAS was 0.69. This indicates that PTBA's company value is almost equivalent to the company value across the energy sector, while PGAS must strive to increase its company value. The average operating profit margin for the entire energy sector is 0.17, while the average operating profit margin for PT BA is 2.55 and the operating profit margin for PGAS is 0.15. This indicates that PTBA's operating profit margin is much larger than the average operating profit margin for the entire energy sector